Monetary Policy and Stock Market Returns: Evidence from ARDL Bounds Testing Approach for the Case of Vietnam - Nguyen, Thuy Thu; Mai, Hong Thi; Tran, Tram Thi Minh (Asian Economic and Financial Review, 2020)
The paper investigates the presence of a cointegrating relationship between monetary policy indicators (namely refinancing rate, money supply, exchange rate, domestic credit, and inflation rate) and VN-Index (the main representative index of Vietnamese stock markets) from August 2000 to December 2018. By using the Autoregressive Distributed-Lag (ARDL) bounds tests, followed by the error correction model for short term dynamics and robustness tests for the stability of the model, the key findings showed that the VN-Index was significantly influenced by all the selected variables in the long term. The outcomes contributed to the current literature by clarifying the determinants of stock prices from monetary policy perspective within the context of an emerging economy and then providing relevant recommendations for enhancing the performance of the Vietnamese stock market. The remaining money supply expansion and the local currency appreciation, while controlling inflation, domestic credit, and reducing refinancing rate can promote the progress of the Vietnamese securities market. Any shock from equilibrium should be adjusted at the considerably high-speed of 48.91% over the next period. It can be considered as a precious reference for policymakers, financial analysts, stock exchange examiners, and any researchers who interested in this field.